A systematic review on Asian's farmers' adaptation practices towards climate change - Mohamed Shaffril, Hayrol Azril; Krauss, Steven Eric; Samsuddin, Samsul Farid (Elsevier, 2018)
Climate change in Asia is affecting farmers' daily routines. Much of the focus surrounding climate change has targeted the economic and environmental repercussions on farming. Few systematic reviews have been carried out on the social impacts of climate change among farmers in Asia. The present article set out to analyse the existing literature on Asian farmers' adaptation practices towards the impacts of climate change. Guided by the PRISMA Statement (Preferred Reporting Items for Systematic reviews and Meta-Analyses) review method, a systematic review of the Scopus and Web of Science databases identified 38 related studies. Further review of these articles resulted in six main themes – crop management, irrigation and water management, farm management, financial management, physical infrastructure management and social activities. These six themes further produced a total of 35 sub-themes. Several recommendations are highlighted related to conducting more qualitative studies, to have specific and a standard systematic review method for guide research synthesis in context of climate change adaptation and to practice complimentary searching techniques such as citation tracking, reference searching, snowballing and contacting experts.